Studies on the delirium-dementia continuum : CNS effects of systemic inflammation on hypocholinergia and chronic neurodegeneration - Field, Robert (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2013)
Peripheral inflammation can signal to the normal, healthy CNS via multiple routes. During ageing and dementia, however, the brain is particularly susceptible to the deleterious effects of such insults. Delirium is an acute and severe disturbance in cognitive function with particular deficits in attention, memory, orientation and perception and a single episode of delirium is predictive of accelerated long-term decline. There are no licensed treatments for delirium and the pathophysiology of this distressing condition remains poorly understood. Dementia and prior cognitive impairment are the major risk factors for delirium, and systemic inflammation is a frequent trigger. The overarching aim of this thesis was to study the interaction between peripheral inflammation and neurodegeneration in order to gain a better understanding of how CNS function is affected by inflammatory insults, with particular relevance for the pathophysiology of delirium during dementia.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.